Drought tolerance of the photosynthetic apparatus of bread wheat (Triticum aestivum L.) lines with introgressions in chromosome 2D from Aegilops tauschii Coss. - S. V. Osipova; A. V. Permyakov; A. V. Rudikovskii; E. G. Rudikovskaya; T. A. Psheni (Вавиловский журнал генетики и селекции, 2025)
One of the ways to increase yield stability of bread wheat under changing climatic conditions is through improving the photosynthesis efficiency. For this purpose, various genetic strategies are used. They include markerassisted selection and the use of the genetic potential of wild wheat relatives. Previously, using introgression wheat lines carrying different segments of chromosome 2D from Aegilops tauschii in the genetic background of the wheat (Triticum aestivum) variety Chinese Spring (CS), we mapped QTLs associated with variability in shoot biomass and gas exchange under contrasting water supply conditions. In this work, by “splitting” the primary introgressions, we obtained secondary introgression CS lines with reduced segments of Ae. tauschii introgressions in the short and long arms of chromosomes 2D. The aim of this study was to investigate the tolerance of the photosynthetic apparatus to soil water deficit in these lines. We estimated the size of drought effect on shoot biomass, gas exchange parameters, photosynthetic pigment content, slow and fast chlorophyll fluorescence parameters, and fast light curve parameters. The results showed that line 1004 with an introgression in chromosome 2DS limited by microsatellite loci Xgwm296 and Xgwm261 was little affected by drought in respect of the chlorophyll (a+b)/carotenoid ratio and primary photosynthetic processes. In line 1005 with a single introgression in the region of the Xgwm261 marker, the chlorophyll (a+b)/carotenoid ratio and indicators of the functional activity of photosystems significantly decreased under water deficiency. The chlorophyll (a+b)/carotenoid ratio, CO2 assimilation rate, and chlorophyll fluorescence parameters remained stable in line 1034 with an introgression in chromosome 2DL near the Xgwm1419 and Xgwm157 loci. In line 1021 with an introgression in the region of the Xgwm539 marker on the same chromosome, we observed a strong negative effect of drought on the rate of CO2 assimilation and indicators of the functional activity of photosystems. The Xgwm1419 and Xgwm296 markers can be recommended for use in marker-assisted breeding for drought tolerance of bread wheat in the cases where Ae. tauschii acts as a donor of genetic material.